Experimental Investigations of the Dental Filling Materials: Establishing Elastic Moduli and Poisson’s Ratios - Száva, Dániel Tamás; Száva, Ioan; Vlase, Sorin; Száva, Andrea (MDPI, Materials, 2023)
The mechanical properties of the dental filling material (DFMs) strongly influence the lifetime and durability of the tooth reparation performed. Among the most significant mechanical characteristics, one has to mention the Poisson’s ratio and the elastic modulus (Young’s modulus). They, during the cyclic mastication load, can prevent or aid in the prevention of secondary dental decays by provoking micro-cracks, the de-bonding of the filling material from the natural dental tissue, as well as fatigue at the level of their interface. The authors performed a scoping analysis of the nowadays-involved experimental methods, together with a critical review, putting in evidence of their advantages and limits. Based on the developments, they propose a new approach in this sense by involving the electronic speckle pattern interferometry (ESPI)/shearography high-accuracy optical method. They illustrate the advantages of this method in establishment of the elastic modulus, but they also propose a high-accuracy methodology in the estimation of Poisson’s ratio. Based on the briefly-illustrated experimental results, one can conclude that ESPI/shearography can become a very useful tool for research, even though it is not a common (nowadays widely applied) method, such as three-point bending or strain gauge methods.
Keywords: dental filling material; DFM; tooth; Poisson’s ratio; Young’s modulus; shearography